2020
DOI: 10.1212/wnl.0000000000010112
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic and neuroimaging findings in patients with COVID-19

Abstract: ObjectiveTo describe neuroimaging findings and to report the epidemiological and clinical characteristics of COVID-19 patients with neurological manifestations.MethodsIn this retrospective multicenter study (10 Hospitals), we included 64 confirmed COVID-19 patients with neurologic manifestations who underwent a brain MRI.ResultsThe cohort included 43 men (67%), 21 women (33%), and the median age was 66 years (range: 20-92). 36 (56%) brain MRIs were considered abnormal, possibly related to SARS-CoV-2. Ischemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
209
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(235 citation statements)
references
References 34 publications
10
209
0
16
Order By: Relevance
“…neuropathogenesis is autoimmune, which would align with steroid responsiveness. The finding of the claustrum sign on brain MRI, not previously reported in a COVID-19 patient, [4][5][6][7][8] provides further support for the idea that acute SARS-CoV-2 infection may present as an autoimmune encephalitis.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…neuropathogenesis is autoimmune, which would align with steroid responsiveness. The finding of the claustrum sign on brain MRI, not previously reported in a COVID-19 patient, [4][5][6][7][8] provides further support for the idea that acute SARS-CoV-2 infection may present as an autoimmune encephalitis.…”
supporting
confidence: 65%
“…CoV-2 5,8. Instead, negative CSF PCR for SARS-CoV-2 may reflect that the underlying https://doi.org/10.1017/cjn.2020.209Downloaded from https://www.cambridge.org/core.…”
mentioning
confidence: 99%
“…About one-third of patients with acute or subacute COVID-19 referred for neuroimaging may show brain abnormalities (25). The results of a large multi-institutional study in France showed ischemic strokes depicted in 27% of patients, leptomeningeal enhancement in 17%, and encephalitis in 13% (26). Large infarcts have been reported in 45% of patients, with lacunar infarcts in 24% and hemorrhagic stroke in another 24% of 38 patients with COVID-19 from a large cohort within the New York health system (27).…”
Section: Neurologic Manifestationsmentioning
confidence: 99%
“…Neurological manifestations of SARS-CoV-2 infection are starting to be systematically recorded and reported, with several initiatives to consolidate and record clinical findings (Ferrarese et al, 2020;Roma´n et al, 2020;Romero-Sa´nchez et al, 2020). Between 30% and 40% of the SARS-CoV-2 patients present neurological symptoms; these can go from mild symptoms including olfactory and gustatory disorders, dizziness, headache, confusion, to a more severe cerebrovascular disease, encephalitis, seizures, or the Guillain-Barr e syndrome (Asadi-Pooya and Simani, 2020; Kremer et al, 2020;Mao et al, 2020). The presence of SARS-CoV-2 viral particles in the CNS has been evidenced in some cases (Benameur et al, 2020;Moriguchi et al, 2020;Wu et al, 2020), with reports showing SARS-CoV-2 presence in CSF (Finsterer and Stollberger, 2020).…”
Section: Severe Acute Respiratory Syndrome-2mentioning
confidence: 99%
“…A mounting body of reports from SARS-CoV-2affected patients is showing that about 30% to 40% of patients develop serious central nervous system (CNS) symptoms, with neurological and neuroradiological alterations confirmed in a large number of cases (Alam et al, 2020;Helms et al, 2020;Jasti et al, 2020;Kremer et al, 2020;Mao et al, 2020;Najjar et al, 2020;Pryce-Roberts et al, 2020;Roma´n et al, 2020;Romero-Sa´nchez et al, 2020;Xiong et al, 2020; and several others). Plasma biomarkers of CNS injury have been shown to be increased in a group of patients with moderate and severe COVID-19 disease (Kanberg et al, 2020).…”
mentioning
confidence: 99%